Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Complete the square to write [tex][tex]$y=3 x^2+12 x+7$[/tex][/tex] in vertex form, [tex][tex]$y=a(x-h)^2+k$[/tex][/tex].

[tex]\[
\begin{array}{l}
y=3\left(x^2+4x\right)+7 \\
y=3\left(x^2+4x+4\right)-3(4)+7 \\
y=3\left(x+2\right)^2-12+7 \\
y=3\left(x+2\right)^2-5
\end{array}
\][/tex]

When the above expression is written in vertex form, [tex][tex]$a$[/tex][/tex] is [tex]3[/tex], [tex][tex]$h$[/tex][/tex] is [tex]-2[/tex], and [tex][tex]$k$[/tex][/tex] is [tex]-5[/tex].


Sagot :

Sure, let's go through the steps to complete the square and write the given quadratic equation in vertex form.

Given equation:
[tex]\[ y = 3x^2 + 12x + 7 \][/tex]

We want to express it in the form [tex]\( y = a(x - h)^2 + k \)[/tex].

### Step-by-Step Solution:

1. Factor out the coefficient of [tex]\(x^2\)[/tex] from the first two terms:
[tex]\[ y = 3(x^2 + 4x) + 7 \][/tex]

2. Complete the square inside the parentheses:
- Take the coefficient of [tex]\(x\)[/tex] (which is 4), divide by 2, and square it. This gives [tex]\((4/2)^2 = 4\)[/tex].
- Add and subtract this value inside the parentheses:
[tex]\[ y = 3(x^2 + 4x + 4 - 4) + 7 \][/tex]
[tex]\[ y = 3((x^2 + 4x + 4) - 4) + 7 \][/tex]

3. Group the complete square and simplify:
[tex]\[ y = 3((x + 2)^2 - 4) + 7 \][/tex]

4. Distribute the 3:
[tex]\[ y = 3(x + 2)^2 - 12 + 7 \][/tex]

5. Simplify the constants:
[tex]\[ y = 3(x + 2)^2 - 5 \][/tex]

Now, the equation is in the vertex form [tex]\( y = a(x - h)^2 + k \)[/tex], where:
- [tex]\( a = 3 \)[/tex]
- [tex]\( h = -2 \)[/tex]
- [tex]\( k = -5 \)[/tex]

So, when the expression is written in vertex form:
- [tex]\( a \)[/tex] is [tex]\( 3 \)[/tex],
- [tex]\( h \)[/tex] is [tex]\( -2 \)[/tex],
- [tex]\( k \)[/tex] is [tex]\( -5 \)[/tex].

[tex]\[ \boxed{3} \quad \boxed{-2} \quad \boxed{-5} \checkmark \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.